2015
DOI: 10.3109/13880209.2014.982298
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of fucoidan against hypoxia-induced apoptosis in H9c2 cardiomyoblast cells

Abstract: Context: Cardiomyocyte apoptosis plays a critical role in the progress of heart diseases. Fucoidan, a complex-sulfated polysaccharide, has been reported to possess potential cardioprotective efficacy in vivo. Objective: The present study determines whether fucoidan could provide cardioprotection on hypoxia-induced cardiomyocyte apoptosis. Materials and methods: H9c2 cardiomyoblast cells were incubated with various concentrations (15, 30, and 60 lg/ml) of fucoidan in a humidified incubator at 37 C with 95% O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
4
8
0
Order By: Relevance
“…The relative mean fold change of the target gene present in test sample with respect to the average control was calculated. The results were presented in terms of 2 −ΔΔCt value that resembles 2 to the power of negative ΔΔCt, as reported earlier (Zhang et al, 2015).…”
Section: In Vitro Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…The relative mean fold change of the target gene present in test sample with respect to the average control was calculated. The results were presented in terms of 2 −ΔΔCt value that resembles 2 to the power of negative ΔΔCt, as reported earlier (Zhang et al, 2015).…”
Section: In Vitro Studiesmentioning
confidence: 84%
“…The experiment was repeated thrice and the mean cell viability was calculated. LDH release assay was also performed using LDH release kit (Thermofisher) as per specified protocol (Zhang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerous studies have found that fucoidan is protective against tissue damage. Zhang et al [23] reported that fucoidan was protective against hypoxia-induced cardiomyocyte apoptosis, and the mechanism might involve protecting the cells from oxidative injury. Rhee et al [24] also reported that fucoidan had protective effects on the radiation-induced damage of blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…[27] reported fucoidan changes the expression patterns of inflammatory cytokines and it attenuate tissue inflammation and fibrosis. Fucoidan-dependent effects are thought to be caused by its scavenging action on ROS and a modulation of inflammation mediator and apoptosis as a radiation mitigator [23, 24, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of fucoidans from Canistrocarpus cervicornis (Camara et al 2011), Lessonia vadosa (Barahona et al 2011), A. nodosum (Yuan & Macquarrie 2015), Dictyota dichotoma, Drosera indica, Iyengaria stellata, Padina pavonia, Sargassum swartzii, Sargassum variegatum, Stoechospermum marginatum, Stokeyia indica, Jolyna laminarioides, Caulerpa taxifolia, Halimeda tuna, Ulva fasciata, Ulva lactuca, Solieria robusta and Melanothamnus afaqhusainii (Tariq et al 2015) demonstrate potential use for the inhibition of free-radical processes in atherosclerosis. Zhang et al (2015a) showed that preincubation of the H9c2 cells with fucoidan prior to hypoxia exposure elevated cell viability and decreased the concentration of malondialdehyde and lactate dehydrogenase.…”
Section: Free Radicalsmentioning
confidence: 99%